(Requirements Of An Educational Environment That Supports Classroom Interaction Among Kindergarten Children From The Teachers’ Point Of View) (Journal of the College of Basic Education, 2024)
An important educational institution, such as a kindergarten, needs an appropriate educational environment that attracts the attention of educators and officials because it is like the fertile land in which the flowers of the future grow, and it must have competent educational cadres to work in this important educational institution, which in turn affects the child’s abilities, talents, growth, psychological, physical, and mental health, and so on.